1997
DOI: 10.1099/00221287-143-2-675
|View full text |Cite
|
Sign up to set email alerts
|

The Mycoplasma hominis P120 membrane protein contains a 216 amino acid hypervariable domain that is recognized by the human humoral immune response

Abstract: The epitope for mAb 26.7D was mapped to the hypervariable domain by expression of various parts of this domain in Escherichia coli using expression vector systems. A polyclonal antiserum (pAb 121) generated against the hypervariable region of Pl20 from PG2l identified the Pl20 homologue in M. hominis PG21. Fusion proteins of the hypervariable and constant parts of the proteins were constructed and tested for reactivity with 21 human sera. Twelve sera reacted with the 7488 hypervariable fusion protein, but only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 30 publications
(37 reference statements)
3
35
0
Order By: Relevance
“…The isolates DC63/ 7488 were shown to have identical hypervariable domains in p120 [11]. These isolates were, in the present study, shown to be in di¡erent p75 RFLP groups.…”
Section: Intraspecies Variation Of P75 Investigated By Pcr and Rflpsupporting
confidence: 53%
See 1 more Smart Citation
“…The isolates DC63/ 7488 were shown to have identical hypervariable domains in p120 [11]. These isolates were, in the present study, shown to be in di¡erent p75 RFLP groups.…”
Section: Intraspecies Variation Of P75 Investigated By Pcr and Rflpsupporting
confidence: 53%
“…Four isolates were, by DNA sequencing, found to have pairwise identical hypervariable domains; 7488/DC63 and SC4/P2. They were speculated to have arisen by horizontal gene transfer [11]. The Vaa protein has a modular composition.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown in clinical isolate 1620 of M. hominis that (i) size variation of Vaa is caused by gain or loss of the tandem repetitive sequences in the central region of this protein; (ii) Cterminal sequence divergence of Vaa leads to antigenic variation among strains, as shown also by others in diverse isolates (2,6); and (iii) single-nucleotide insertions or deletions in a polyadenine tract within the 5Ј end of the vaa coding region create reversible frameshift mutations causing variable expression of Vaa, with concurrent alterations of M. hominis adherence to human cells in vitro (29). The abundant P120 surface lipoprotein contains a hypervariable N-terminal region, two central semivariable domains, and a highly conserved C-terminal region (3,12). The hypervariable domain of P120 is exposed on the mycoplasma surface and is the target of a strong humoral response in the human host, while the conserved C-terminal region is not.…”
mentioning
confidence: 79%
“…Comparison of p120 alleles in different strains has revealed that P120 contains a hypervariable Nterminal region and a highly conserved C-terminal region (12). The hypervariable region of P120 is exposed on the mycoplasma surface and is immunodominant in the human host, while the highly conserved C-terminal region of P120 is apparently not a target of the humoral immune response.…”
Section: Phase Variation Of P56 Surface Epitope Display Is Not Relatementioning
confidence: 99%
See 1 more Smart Citation